2016
DOI: 10.1007/s10943-016-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use in College: The Relationship Between Religion, Spirituality, and Proscriptive Attitudes Toward Alcohol

Abstract: Developing interventions to address the problem of college drinking requires the identification of contributing factors to drinking behavior. It is believed that religion and spirituality (R/S) play a role, but the mechanism is unclear. Using a multi-dimensional R/S measure, an alcohol behavior inventory, and a religious affiliation proscription question, this study was designed to dive deeper into this connection. This study found that religious singing/chanting and reading sacred text were the best predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…A limitation of the current model is that it includes only age and gender as individual characteristics. Other characteristics such as religion, race/ethnicity, and socioeconomic status are relevant with regard to injunctive norms (Kathol & Sgoutas-Emch, 2017; Meyers, Brown, Grant, & Hasin, 2017; Pedersen, Bakken, & von Soest, 2015). While it is anticipated that these characteristics will be included in future versions of the model, it is important to note that scarcity of empirical evidence on injunctive drinking norms in these subgroups poses a challenge to informing respective priors of the model.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the current model is that it includes only age and gender as individual characteristics. Other characteristics such as religion, race/ethnicity, and socioeconomic status are relevant with regard to injunctive norms (Kathol & Sgoutas-Emch, 2017; Meyers, Brown, Grant, & Hasin, 2017; Pedersen, Bakken, & von Soest, 2015). While it is anticipated that these characteristics will be included in future versions of the model, it is important to note that scarcity of empirical evidence on injunctive drinking norms in these subgroups poses a challenge to informing respective priors of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Se encontró también correlación negativa significativa entre las creencias espirituales y la cantidad de bebidas alcohólicas por ocasión, lo que significa que a mayores creencias espirituales menor es la cantidad de bebidas alcohólicas consumidas por ocasión, lo que puede deberse a que quienes tienen mayores creencias espirituales tienden a conductas saludables, si bien consumen no lo hacen de forma riesgosa o dañina (17) . Así mismo se observó que existe correlación significativa entre las necesidades espirituales y el índice de consumo dañino lo que significa que a mayores necesidades espirituales mayor es el consumo dañino, lo que puede deberse a que la subescala de necesidades espirituales está centrada en el yo y solo hace referencia a la definición de preferencias y búsqueda de intereses personales, y no a las premisas espirituales como el buscar el bien del otro antes que el propio (18) .…”
Section: Discussionunclassified
“…Religious activities have been investigated as well. For instance, religious chanting/singing and reading the sacred texts are associated with lower alcohol consumption in general [72]; however, it was alco reported that frequent prayer can aid alcohol consumption reduction for moderate drinkers but not heavy drinkers [66].…”
Section: Religious Influencementioning
confidence: 99%
“…One's feelings toward religion and its importance in life may moderate the effects of religiosity. For instance, those who believed their religious heritage is prescriptive drank less alcohol and had stronger religious characteristics [72]. On the other hand, students who reported that religion played a minor role in their lives were more likely to have recently consumed alcohol [67].…”
Section: Religious Influencementioning
confidence: 99%